A Smartphone-Based Sensor With an Uncooled Infrared Thermal Camera for Accurate Temperature Measurement of Pig Groups - Jiao, Fu; Wang, Kun; Shuang, Feng; Dong, Daming; Jiao, Leizi (Frontiers in Physics, 2022)
Low-cost uncooled infrared thermal cameras show large application potential for the rapid diagnosis of pig diseases. However, with the increase of ambient temperature and absorbing infrared radiation, almost all of them produce severe thermal drift and provide poor accuracy of temperature measurement. In addition, the unknown surface emissivity on a pig’s body can also bring measuring errors. In this paper, an uncooled infrared thermal camera with an accuracy of 3℃ was used to develop a smartphone-based sensor for measuring pig’s temperature. Based on this sensor, we propose a system combined with internal calibration for real-time compensating the thermal drift and altering spectrum for eliminating the influence of unknown surface emissivity to improve the accuracy of temperature measurement. After calibration, the accuracy of this sensor was improved from 3°C to 0.3°C without knowing the emissivity. We used this sensor to successfully identify pigs with abnormal temperatures on a livestock farm, which indicated that our proposed methods may be widely employed for rapid temperature screening and disease diagnosis of pig diseases.